Clustering Techniques For Channel Equalisation Using Fuzzy And Minimal Radial Basis Function Networks - Pu, Chuan Chin (2004)
Digital communication over bandlimited channels often encounter the problem of intersymbol interference (ISI), which can degrade signal quality down to an unacceptable level. As such, a channel equaliser is usually used at the receiving end to mitigate the ISI. This thesis studies adaptive channel equalisation based on softcomputing techniques.